Relationships between selected speed strength performance tests and temporal variables in maximal running velocity - Faccioni, A.
The relationships between selected sprint specific bounding exercises and sprint performance were analysed using fourteen sprint athletes (7 elite performers, 7 sub-elite performers). Subjects were required to perform sprints over 60m, Counter Movement Jumps with and without loading (20kg), High Speed Alternate Leg Bounding over 30m and High Speed Single Leg Hopping over 20m. All athletes were subject to anthropometric measurement (Height, Weight and Leg Length).